Brand Personality in Politics : Scale Development and Validation - Gopal, Krishan; Verma, Rajesh (Indian Journal of Marketing, 2018)
The ever increasing market dynamics and very tough competition has increased the role of brands to a supreme level. Researchers like Plummer (1985) and Aaker (1997) highlighted the critical role of brand personality in building loyalty and competitive advantage. This article focused on whether the concept of branding is applicable to political parties. It highlighted the problems associated with the managerial approach to branding in politics and advocated an alternative form of consumer learningÂ perspective. This approach is used to describe the process and reasons to form brand personalities in politics. Important prior influences on the brand personality were highlighted, that is, events, advertising, endorsers, and prevalent users and their impact upon the learning of voters regarding brand personality of political parties. After conceptualizing political party brand personality, the paper examined whether the available scale of brand personality was suitable in context of Indian politics.